Can't spell treason without tea : a cozy fantasy steeped with love - Thorne, Rebecca (Thorne, Rebecca, 1991- Tomes and tea novel, 2024)
"All Reyna and Kianthe want is to open a bookshop that serves tea. Worn wooden floors, plants on every table, firelight drifting between the rafters ... all complemented by love and good company. Thing is, Reyna works as one of the Queen's private guards, and Kianthe is the most powerful mage in existence. Leaving their lives isn't so easy. But after an assassin takes Reyna hostage, she decides she's thoroughly done risking her life for a self-centered queen. Meanwhile, Kianthe has been waiting for a chance to flee responsibly -- all the better that her girlfriend is on board. Together, they settle in Tawney, a town nestled in the icy tundra near dragon country, and open the shop of their dreams. What follows is a cozy tale of mishaps, mysteries, and a murderous queen throwing the realm's biggest temper tantrum. In a story brimming with hurt/comfort and quiet fireside conversations, these two women will discover just what they mean to each other ... and the world."--Back cover